2014
DOI: 10.3892/ijmm.2014.1659
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological review of 33 patients with vulvar melanoma identifies c-KIT as a prognostic marker

Abstract: Vulvar melanoma is the second most common vulvar cancer. Patients with vulvar melanoma usually present with the disease at a late stage and have a poor prognosis. The prognostic predictors reported in the literature are not unequivocal and the role of lichen sclerosus and c-KIT mutations in the aetiology of vulvar melanoma is unclear. Breslow staging currently seems to be the most adequate predictor of prognosis. We thus performed a clinicopathological and literature review to identify suitable predictors of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 76 publications
2
36
0
1
Order By: Relevance
“…Nevertheless, CD117 overexpression (which was significantly associated with KIT mutation) retained its significance as a marker for improved PFS in multivariate analysis. Whereas KIT expression has been proposed as a marker of poor disease‐free survival in one series, another study found no association between KIT expression or mutational status with OS . Variabilities of antibodies and staining methods might account for these differences.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, CD117 overexpression (which was significantly associated with KIT mutation) retained its significance as a marker for improved PFS in multivariate analysis. Whereas KIT expression has been proposed as a marker of poor disease‐free survival in one series, another study found no association between KIT expression or mutational status with OS . Variabilities of antibodies and staining methods might account for these differences.…”
Section: Discussionmentioning
confidence: 96%
“…Studies targeting BRAF , NRAS and KIT have shown that vulvovaginal melanomas, in contrast to conventional cutaneous melanomas, typically harbor wild-type BRAF , while KIT and NRAS mutations are present in approximately 20% of cases (Heinzelmann-Schwarz et al , 2014, Tseng et al , 2014, van Engen-van Grunsven et al , 2014). Conversely, separate studies analyzing the same genes in AGN have shown frequent BRAF mutations, particularly V600E (Nguyen et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In line with trends toward more conservative surgery for cutaneous melanomas, there is a trend toward more conservative resection of vulvar melanomas [57–59]. Primary lesions should be treated by radical local excision, with margins around the lesion of at least 1 cm.…”
Section: Special Situationsmentioning
confidence: 99%